Fenomena Manusia Silver Sebagai Realisasi dari Dramaturgi dan Psikososial - Nadia Khalishah Fitri; Rijal Abdilah; Tugimin Supriyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The phenomenon of manusia silver (silver-painted street performers) has become an increasingly prevalent social reality in urban areas of Indonesia, reflecting the social, economic, and psychological dynamics of individuals living under conditions of limitation. This study aims to understand the manusia silver phenomenon as a manifestation of dramaturgy and psychosocial dynamics, particularly in the context of self-identity formation and role confusion. This research employs a qualitative method with a phenomenological approach. Participants were selected using snowball sampling, with the criteria being manusia silver individuals residing in Bekasi City. Data were collected through in-depth interviews, observation, and literature review, and subsequently analyzed qualitatively. The results indicate that the role of manusia silver is formed as an adaptive response to economic pressure, limited educational attainment, lack of employment opportunities, and weak social support. From Erving Goffman’s dramaturgical perspective, the activities of manusia silver in public spaces represent the front stage through silver-painted bodies and symbolic behaviors designed to create certain impressions, while their private lives outside these activities represent the back stage. From Erik Erikson’s psychosocial perspective, most participants are in adolescence to early adulthood, a phase vulnerable to role confusion, and tend to occupy an identity foreclosure status, in which the identity as manusia silver is adopted without optimal exploration. Nevertheless, participants still hold hopes for a better future, although these hopes are not yet accompanied by clear planning.